ANALISIS PENGENDALIAN KUALITAS PRINTING HOUSING TOP MELITA PADA PT LEON TEKNOLOGI GLOBAL - Laia, Saferia Suiman; Asmarawati, Citra Indah (LPPM Universitas Putera Batam, 2023)
PT Leon Teknologi is a company engaged in the coating or polishing of raw materials for parts and even assy such as spray painting which has several large customers in the city of Batam, HSG TOP Melitta is a customer in the field of spray painting who has just collaborated with PT Leon in 2020 In terms of quality control issues at PT Leon, visual reject is the main contribution, with a reject rate of 3.5% of the total quantity during the last 6 months of production in the spray painting process, such as Crack on, scratch, White/Black dot and Over painting on Housing Top melitta after printing, Factors Causing Defects on Fishbone analysis, namely from scratch From Human Factors, scratch defects are caused by a lack of production operator training which causes inaccurate operator handling and a lack of understanding of the types of product defects that occur in the production process and methods, namely The lack of clarity on work instructions for the spray painting process caused the spray painting process to be inconsistent with operator procedures and finally the material, which is a type of material that is easily scratched, needs to be reviewed for work instructions on the Melitta upper housing. The Crack factor from Crack is likely to occur in mixing paint with thinner which has a ratio of 1 (Paint): 3 (Thinner) and in general some Spray Painting uses a ratio of 1 (Paint) : 1.3 (Thinner) and some experiments use a ratio of paint and thinner the latest so that out of 30 samples no Crack was Found